Successful treatment of out-of-hospital cardiac arrest is still based on quick activation of the chain of survival - Laura Borgstedt; Stefan J. Schaller; Stefan J. Schaller; Daniel Goudkamp; Kristina Fuest; Bernhard Ulm; Bettina Jungwirth; Manfred Blobner; Manfred Blobner; Sebastian Schmid (Frontiers Media S.A., 2023)
Background and goal of studyCardiopulmonary resuscitation (CPR) in prehospital care is a major reason for emergency medical service (EMS) dispatches. CPR outcome depends on various factors, such as bystander CPR and initial heart rhythm. Our aim was to investigate whether short-term outcomes such as the return of spontaneous circulation (ROSC) and hospital admission with spontaneous circulation differ depending on the location of the out-of-hospital cardiac arrest (OHCA). In addition, we assessed further aspects of CPR performance.Materials and methodsIn this monocentric retrospective study, protocols of a prehospital physician-staffed EMS located in Munich, Germany, were evaluated using the Mann-Whitney U-test, chi-square test, and a multifactor logistic regression model.Results and discussionOf the 12,073 cases between 1 January 2014 and 31 December 2017, 723 EMS responses with OHCA were analyzed. In 393 of these cases, CPR was performed. The incidence of ROSC did not differ between public and non-public spaces (p = 0.4), but patients with OHCA in public spaces were more often admitted to the hospital with spontaneous circulation (p = 0.011). Shockable initial rhythm was not different between locations (p = 0.2), but defibrillation was performed significantly more often in public places (p < 0.001). Multivariate analyses showed that hospital admission with spontaneous circulation was more likely in patients with shockable initial heart rhythm (p < 0.001) and if CPR was started by an emergency physician (p = 0.006).ConclusionThe location of OHCA did not seem to affect the incidence of ROSC, although patients in public spaces had a higher chance to be admitted to the hospital with spontaneous circulation. Shockable initial heart rhythm, defibrillation, and the start of resuscitative efforts by an emergency physician were associated with higher chances of hospital admission with spontaneous circulation. Bystander CPR and bystander use of automated external defibrillators were low overall, emphasizing the importance of bystander education and training in order to enhance the chain of survival.